Mempelajari Hubungan Kematangan dan Berat Jenis Durian (Durio zibhetinus, Murr) - Bambang Haryanto; I. Wayan Budiastra (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2000)
The study was conducted to determine the ripeness of durian (durio zibhetinus) by spesific gravity. Total sample were 32 durians, consited of 16 unripe durians and 16 ripe durians. Durians was colected from Bogor. Spesific gravity of durians was measured by water displacement method and then the durians were opened to check the ripeness. Firmness and total soluble solid were determined to reveal the ripeness of flesh. The spesific gravity of ripe durian was (0.824 ± 0.03) g/cm3. The firmness of ripe durian was (5.99 ± 4.04) N and unripe one was (43.48 ± 5.39) N. The total soluble solid of ripe durian was (43.48 ± 5.39) % brix and unripe one was (6.91 ± 1.30) % brix. The relationship of spesific gravity (BJ) with the flesh of durian firmness and total soluble solid were fairly high with the correlation coefficients of 0.86 and 0.91 respectively.